2014
DOI: 10.1109/tuffc.2014.2930
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided photoacoustic imaging: current state and future development

Abstract: Photoacoustic imaging, frequently coregistered with ultrasonic imaging, can provide functional and cellular/molecular information about tissue within the anatomical landmarks of an imaged region. This review details the fundamentals of photoacoustic imaging and its most promising imaging applications. Particular attention is paid to photoacoustic imaging's relationship with ultrasound, focusing on distinct differences and similarities between the two modalities and highlighting the mutual benefit of using both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 180 publications
0
69
0
Order By: Relevance
“…Photoacoustic imaging has been widely studied fused with variable medical fields such as US and microscopy [26], [27]. Recently, Kang et al investigated PAI-visualized microcalcifications in breast tissues in a study which revealed the absorbance differences between microcalcifications and surrounding tissues [15], [28].…”
Section: Discussionmentioning
confidence: 99%
“…Photoacoustic imaging has been widely studied fused with variable medical fields such as US and microscopy [26], [27]. Recently, Kang et al investigated PAI-visualized microcalcifications in breast tissues in a study which revealed the absorbance differences between microcalcifications and surrounding tissues [15], [28].…”
Section: Discussionmentioning
confidence: 99%
“…101 Similarly, photonic-based cancer therapies, such as laser induced photodynamic therapy (PDT) 105,106 and photothermal therapy (PTT), 107 can also beneÂŻt from PAI, as PAI can monitor the drug distribution simultaneously during the therapy without the use of additional contrast agents. Furthermore, PAI can be combined with other imaging modalities, such as°uorescence imaging 81,92,108 and US imaging, 57,58,64,81,109 to provide complementary information and optimal image quality. Through PAI, minimally invasive onsite prostate cancer diagnosis with enhanced sensitivity and speciÂŻcity may be achieved.…”
Section: Future Outlookmentioning
confidence: 99%
“…The illuminated tissue experiences thermal expansion, which in turn produces acoustic waves that are received by a conventional ultrasound array transducer, forming a map of optical absorption which can be used either independently or in conjunction with ultrasound [49]. Penetration depths in photoacoustic imaging are approximately 2 cm [50].…”
Section: High Resolution Vascular Imaging Technologiesmentioning
confidence: 99%